Transversal competencies in university: validation of a questionnaire for its evaluation - Solanes-Puchol, Ángel (2022)
Introduction: Transversal competences constitute a key element for the academic-professional training and sociolabour insertion of university students. Numerous studies reveal a gap between the level of generic skills and the level demanded by the labor market. The evaluation of these competencies becomes essential in university education, so it is necessary to have valid evaluation tools. Objective: To develop a measurement instrument that effectively evaluates said competencies. Method: a questionnaire has been designed based on the model used by Solanes et al. (2008), using the Delphi method to assess content validity. The test has been administered to 946 students, dividing this sample into four equal subgroups to carry out two parallel analyzes and two confirmatory factor analyzes. Results: The final scale is composed of 38 items that explain 53.1% of the variance, with a McDonald’s omega of .94. The parallel analysis reveals a factorial structure of five factors. Likewise, the confirmatory factor analyzes provide evidence of validity on the internal structure of the questionnaire (CMIN/DF = 1.903; RMSEA = .062; CFI = .91; PNFI = .657; NFI = .90; RMR = .042; PGFI = .88). Discussion: An instrument is provided that meets the specifications to be considered a valid and reliable tool, which evaluates the transversal skills most demanded by the labor market.